2020
DOI: 10.1021/acs.jpclett.0c00061
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Rationalizing the Differing Surface Reactions of Low-Energy Electrons and Ions with an Organometallic Precursor

Abstract: Surface reactions of electrons and ions with physisorbed organometallic precursors are fundamental processes in focused electron and ion beam-induced deposition (FEBID and FIBID, respectively) of metal-containing nanostructures. Markedly different surface reactions occur upon exposure of nanometer-scale films of (η5-Cp)­Fe­(CO)2Re­(CO)5 to low-energy electrons (500 eV) compared to argon ions (860 eV). Electron-induced surface reactions are initiated by electronic excitation and fragmentation of (η5-Cp)­Fe­(CO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(63 citation statements)
references
References 47 publications
2
59
2
Order By: Relevance
“…In a recent paper, we compared the low energy (<1 keV) electron-and argon ion-induced decomposition reactions of thin films of adsorbed CpFe(CO) 2 Re(CO) 5 on a cooled gold substrate. 37 This study revealed that the electron and argon ion-induced decomposition of adsorbed CpFe(CO) 2 Re(CO) 5 were significantly different, giving support to the collision cascade model dominating deposition in the ion-limited regime of FIBID. To explore the extent to which these differences apply to other precursors we have used in situ XPS in the present investigation to compare and contrast the low energy electron-(500 eV) and Ar + (1200−3000 eV) induced reactions with thin films of adsorbed Fe(CO) 5 on a cooled (143 K) Au substrate.…”
Section: ■ Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…In a recent paper, we compared the low energy (<1 keV) electron-and argon ion-induced decomposition reactions of thin films of adsorbed CpFe(CO) 2 Re(CO) 5 on a cooled gold substrate. 37 This study revealed that the electron and argon ion-induced decomposition of adsorbed CpFe(CO) 2 Re(CO) 5 were significantly different, giving support to the collision cascade model dominating deposition in the ion-limited regime of FIBID. To explore the extent to which these differences apply to other precursors we have used in situ XPS in the present investigation to compare and contrast the low energy electron-(500 eV) and Ar + (1200−3000 eV) induced reactions with thin films of adsorbed Fe(CO) 5 on a cooled (143 K) Au substrate.…”
Section: ■ Introductionmentioning
confidence: 55%
“…The similar rate and extent of carbon and oxygen loss strongly suggests that this process is a consequence of CO desorption, consistent with previous studies of other metal carbonyls exposed to low energy electrons. 24,[29][30][31]37 Figure 2b plots the relative abundance of graphitic carbon (open squares) and oxide oxygen (blue squares) upon irradiation with 500 eV electrons, as measured by the graphitic C(1s) and oxide O(1s) XPS peaks (Figure 1), respectively. These two species show a near identical kinetic dependence, indicating that they are likely produced by the same process and with equal efficiency.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be achieved through cooling the substrate below the precursor condensation temperature. [19][20][21][22][23][24] This Cryo-FIBID approach holds an enormous potential for rapid patterning of metallic micro/nano-deposits. For example, optimized W-C cryo-deposits with a resistivity of 800 •cm were obtained using 50 C/cm 2 Ga + dose and applied as electrical contacts to measure semiconducting nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…The viability of Pt deposition by Cryo-FIBID is reinforced by previous investigations that have demonstrated that focused electron beam irradiation under cryogenic conditions (Cryo-FEBID) of the (CH 3 ) 3 Pt(CpCH 3 ) precursor is feasible [ 16 ]. Additionally, recent theoretical work has emphasized the advantages of ion versus electron precursor decomposition under cryogenic conditions for the metallic content of the deposits [ 17 ].…”
Section: Introductionmentioning
confidence: 99%